STUDY OF LACTOSE CRYSTALLIZATION IN CONCENTRATED WHEY - Perrone, Ítalo Tuler; Pereira, João Pablo Fortes; Renhe, Isis Rodrigues Toledo; Francisquini, Júlia d’Almeida; Stephani, Rodrigo; de Carvalho, Antônio Fernandes (Revista do Instituto de Laticínios Cândido Tostes, 2017)
The kinetics of lactose crystal growth in concentrated whey were studied in two stages. The first took place in a bench-top crystallizer and the second in an industrial crystallizer using concentrated whey obtained by vacuum evaporation, consisting of 3 treatments: crystallization by primary nucleation, by secondary nucleation with the addition of 0.05% and with the addition of 0.1% microcrystalline lactose. The average size of the crystals remained between 60.7 mm and 63.8 mm. The percentage of crystallization was greater in the secondary nucleation process than in the primary nucleation, where crystallization stabilized first. Mathematical equations which independently related crystallization times of the concentrated whey to the concentrations of soluble solids, crystallization percentage and mass of lactose in water were established, that can be used in the industrial setting to process whey. The kinetics of lactose crystal growth was not well described by models of first or second order reactions.